Polylactic acid fabric and production process thereof
By using flame retardant antibacterial agent APP@CS/Ag-g-PDEAMP in polylactic acid fabrics, combining ammonium polyphosphate, chitosan and silver ions, the shortcomings of flame retardant and antibacterial properties of polylactic acid fibers are solved, and the fabric is realized Highly efficient flame retardant and antibacterial properties.
Patent Information
- Application Number
- CN202411576218.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-31
AI Technical Summary
Polylactic fibers have shortcomings in flame retardant and antibacterial properties, which limit their application in high demand areas.
The flame retardant antibacterial agent APP@CS/Ag-g-PDEAMP is melt blended with polylactic acid slices, and the fabric is improved through the synergistic effect of ammonium polyphosphate, chitosan, silver ions and diethyl methylphosphonate acrylate. Flame retardant and antibacterial properties.
It significantly improves the flame retardancy and antibacterial properties of polylactic acid fabrics, forms a dense carbon layer and stable antibacterial effect, and is suitable for high-demand textile materials.
Smart Images

Figure BDA0005121875070000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, and in particular to a polylactic acid fabric and a production process thereof. Background Art
[0002] As a necessity for human life, textiles are used in huge quantities, are difficult to recycle, and have a great impact on the environment. Therefore, vigorously developing new biodegradable textile materials has become one of the current trends in the development of world textile technology. In recent years, the new fiber material polylactic acid fiber has attracted the attention and favor of the global textile material industry. Polylactic acid fiber is a degradable chemical fiber material made from renewable grains such as corn. It overcomes the disadvantage of polymer materials relying on petrochemical resources. It can be completely degraded in water or soil without causing pollution to the environment. It can be widely used in biomedicine, packaging materials, clothing and home textiles, and other fields. It is one of the most promising bio-based degradable materials to date.
[0003] However, the chemical structure and element composition of polylactic acid determine that it has the same flammable defect as general polymer materials (limited oxygen index is about 20.5%, vertical combustion grade is NR), which limits its application in fields with high flame retardancy requirements, so polylactic acid flame retardant modification is very necessary. And as people pay more attention to health, antibacterial functional requirements are also put forward for textiles, but polylactic acid fabrics have poor antibacterial properties, which seriously hinders their marketization process. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the object of the present invention is to provide a polylactic acid fabric and a production process thereof, so as to solve the technical problems of poor flame retardancy and poor antibacterial properties of the polylactic acid fabric.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A production process of polylactic acid fabric, characterized in that it comprises the following steps:
[0007] The flame retardant antibacterial agent APP@CS / Ag-g-PDEAMP is melt-blended with polylactic acid slices to obtain flame retardant antibacterial polylactic acid slices; the flame retardant antibacterial polylactic acid slices are dried, melt-spun and woven to obtain polylactic acid fabrics.
[0008] Furthermore, the preparation steps of the flame retardant antibacterial agent APP@CS / Ag-g-PDEAMP include:
[0009] S1. Ammonium polyphosphate (APP) and chitosan (CS) self-assemble to obtain APP@CS:
[0010] CS was dissolved in 1 wt% acetic acid solution to obtain a CS solution, APP was evenly dispersed in deionized water to obtain an APP solution, and the APP solution was added dropwise to the CS solution, stirred evenly, centrifuged, and washed with deionized water to obtain APP@CS;
[0011] Furthermore, the mass ratio of CS to APP is 1:10;
[0012] S2. APP@CS complexes with Ag to form APP@CS / Ag:
[0013] APP@CS was added into deionized water; then AgNO3 solution was added and stirred to mix; then NaBH4 solution was added dropwise and stirred to react for 10-15 min; ammonia water was added to adjust the pH value to alkaline so that a precipitate appeared in the solution, and the solution was centrifuged to obtain a solid substance, which was washed with distilled water and acetone and dried at room temperature for 10-12 h to obtain APP@CS / Ag.
[0014] Furthermore, the dosage ratio of the APP@CS, AgNO3 solution and NaBH4 solution is 0.1 g:16-20 mL:0.8-1 mL; the concentration of the AgNO3 solution is 10 mmol / L, and the concentration of the NaBH4 solution is 100 mmol / L.
[0015] S3, silane coupling agent KH570 modified APP@CS / Ag to obtain APP@CS / Ag-KH570:
[0016] APP@CS / Ag was ultrasonically dispersed in anhydrous ethanol, KH570 was added and stirred for 8-10 hours, filtered, washed with anhydrous ethanol, and dried for 10-12 hours to obtain APP@CS / Ag-KH570;
[0017] Further, the amount of KH570 is 4-6wt% of APP@CS / Ag;
[0018] S4. APP@CS / Ag-KH570 was grafted with poly(diethyl methylphosphonate) acrylate to obtain APP@CS / Ag-g-PDEAMP:
[0019] APP@CS / Ag-KH570 and diethyl methylphosphonate acrylate monomer (DEAMP) were mixed in a mass ratio of 1:1, and anhydrous ethanol and azobisisobutyronitrile (AIBN) were added; the mixture was stirred and heated to 75-80°C under nitrogen protection, reacted for 10-12 hours, and then filtered, washed with methanol, washed with anhydrous ethanol, and dried for 10-12 hours to obtain APP@CS / Ag-g-PDEAMP;
[0020] Furthermore, the mass ratio of the APP@CS / Ag-KH570 to AIBN is 1:40;
[0021] Furthermore, the DEAMP is synthesized by the following steps: diisopropyl (hydroxymethyl)phosphonate, dichloromethane and triethylamine are stirred in an ice-salt bath at -5°C for 0.5-1h to obtain a mixed solution; then acryloyl chloride and dichloromethane are evenly mixed and slowly added dropwise to the mixed solution, and after the addition is completed, the system temperature is maintained at -5°C and stirred for 1-2h; then the temperature is raised to 30-35°C and stirred for 10-12h; after the reaction is completed, the DEAMP is obtained by washing with water and rotary evaporation;
[0022] Furthermore, the usage ratio of diisopropyl (hydroxymethyl)phosphonate, dichloromethane and triethylamine is 0.1 mol:50 mL:0.1 mol; the usage ratio of acryloyl chloride to dichloromethane is 0.1 mol:10 mL.
[0023] Further, the temperature of the melt blending is 160°C-190°C;
[0024] The amount of APP@CS / Ag-g-PDEAMP used is 0.25-1wt% of the total mass of the polylactic acid slice.
[0025] Furthermore, the flame retardant and antibacterial polylactic acid slices are dried at 110-120° C. for 10-12 hours;
[0026] The melt spinning temperature is 180-200°C.
[0027] A polylactic acid fabric is prepared by the above production process.
[0028] Beneficial effects of the present invention:
[0029] (1) The present invention prepares the flame retardant and antibacterial agent APP@CS / Ag-g-PDEAMP for use in the production process of polylactic acid fabrics. The produced polylactic acid fabrics have excellent flame retardancy and antibacterial properties and can be widely used in textile materials.
[0030] (2) The flame retardant and antibacterial agent prepared by the present invention uses ammonium polyphosphate and chitosan as the acid source and carbon source of the flame retardant system, respectively; when ammonium polyphosphate is heated, it will decompose to produce acidic substances such as phosphoric acid, metaphosphoric acid and polymetaphosphoric acid, which can promote the dehydration and carbonization of polylactic acid, thereby forming a dense carbon layer on the surface of the material. This carbon layer can not only effectively isolate oxygen and heat, but also inhibit the release of combustible gases, thereby significantly improving the flame retardant properties of polylactic acid; when chitosan is heated, it can form a stable carbon layer to prevent the further spread of flames; therefore, ammonium polyphosphate can synergistically act with chitosan to achieve a highly efficient flame retardant effect.
[0031] (3) The flame retardant antibacterial agent prepared by the present invention combines chitosan with silver ions to produce a synergistic antibacterial effect: chitosan can adsorb and fix silver ions to prevent them from being released too quickly, thereby prolonging the duration of the antibacterial effect; at the same time, the antibacterial properties of chitosan itself can also complement the antibacterial properties of silver ions to improve the overall antibacterial effect.
[0032] (4) The flame retardant and antibacterial agent prepared by the present invention is modified by KH570 and grafted with poly(diethyl methylphosphonate) acrylate, which improves the compatibility of the flame retardant and antibacterial agent with polylactic acid, thereby improving the dispersibility of the flame retardant and antibacterial agent in polylactic acid, and can better exert the flame retardant and antibacterial effect. At the same time, poly(diethyl methylphosphonate) acrylate plays a certain flame retardant role. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The diethyl methylphosphonate acrylate monomer (DEAMP) used in the following examples and comparative examples is synthesized by the following steps: 0.1 mol of diisopropyl (hydroxymethyl)phosphonate, 50 mL of dichloromethane and 0.1 mol of triethylamine are stirred in an ice-salt bath at -5°C for 1 hour to obtain a mixed solution; then 0.1 mol of acryloyl chloride and 10 mL of dichloromethane are mixed evenly and slowly added dropwise to the mixed solution. After the addition is completed, the system temperature is maintained at -5°C and stirred for 2 hours; then the temperature is raised to 35°C and stirred for 12 hours; after the reaction is completed, DEAMP is obtained by washing with water and rotary evaporation.
[0035] Example 1
[0036] This embodiment provides a polylactic acid fabric, which is prepared by the following production process:
[0037] The flame retardant antibacterial agent APP@CS / Ag-g-PDEAMP is melt-blended with polylactic acid slices at 180°C to obtain flame retardant antibacterial polylactic acid slices, wherein the amount of APP@CS / Ag-g-PDEAMP is 0.25wt% of the total mass of the polylactic acid slices; the flame retardant antibacterial polylactic acid slices are dried at 120°C for 12h, melt-spun at 180-200°C, and woven to obtain polylactic acid fabrics.
[0038] The preparation steps of the flame retardant antibacterial agent APP@CS / Ag-g-PDEAMP include:
[0039] S1. APP and chitosan CS self-assemble to obtain APP@CS:
[0040] 1 g CS was dissolved in 1 wt% acetic acid solution to obtain CS solution, 10 g APP was evenly dispersed in 200 mL deionized water to obtain APP solution, the APP solution was added dropwise to the CS solution, stirred evenly, centrifuged, and washed with deionized water to obtain APP@CS;
[0041] S2. APP@CS complexes with Ag to form APP@CS / Ag:
[0042] 0.1 g APP@CS was added to 100 mL deionized water; then 16 mL of 10 mmol / L AgNO3 solution was added and stirred to mix; then 0.8 mL of 100 mmol / L NaBH4 solution was added dropwise and stirred for 15 min; ammonia water was added to adjust the pH value to alkaline to cause precipitation in the solution, and the solution was centrifuged to obtain a solid substance, which was washed with distilled water and acetone and dried at room temperature for 12 h to obtain APP@CS / Ag;
[0043] S3, silane coupling agent KH570 modified APP@CS / Ag to obtain APP@CS / Ag-KH570:
[0044] 1 g APP@CS / Ag was ultrasonically dispersed in 100 mL of anhydrous ethanol, 0.04 g KH570 was added and stirred for 10 h, filtered, washed with anhydrous ethanol, and dried for 12 h to obtain APP@CS / Ag-KH570;
[0045] S4. APP@CS / Ag-KH570 was grafted with poly(diethyl methylphosphonate) acrylate to obtain APP@CS / Ag-g-PDEAMP:
[0046] 1 g APP@CS / Ag-KH570 and 1 g DEAMP were mixed, and 100 mL anhydrous ethanol and 0.025 g AIBN were added; the mixture was stirred and heated to 80 °C under nitrogen protection, and after reacting for 10 h, the mixture was filtered, washed with methanol, washed with anhydrous ethanol, and dried for 12 h to obtain APP@CS / Ag-g-PDEAMP.
[0047] Example 2
[0048] Compared with Example 1, the present embodiment is different in that the steps of "adding 16 mL of 10 mmol / L AgNO3 solution, stirring to mix; then dropping 0.8 mL of 100 mmol / L NaBH4 solution" in step S2 is changed to "adding 18 mL of 10 mmol / L AgNO3 solution, stirring to mix; then dropping 0.9 mL of 100 mmol / L NaBH4 solution"; the remaining raw materials and preparation process are the same as those in Example 1.
[0049] Example 3
[0050] Compared with Example 2, the present embodiment is different in that the steps of "adding 16 mL of 10 mmol / L AgNO3 solution, stirring to mix; then dropping 0.8 mL of 100 mmol / L NaBH4 solution" in step S2 is changed to "adding 20 mL of 10 mmol / L AgNO3 solution, stirring to mix; then dropping 1 mL of 100 mmol / L NaBH4 solution"; the remaining raw materials and preparation process are the same as those in Example 1.
[0051] Example 4
[0052] The difference between this embodiment and embodiment 3 is that "adding 0.04 g KH570" in step S3 is changed to "adding 0.05 g KH570"; the remaining raw materials and preparation process remain the same as those in embodiment 3.
[0053] Example 5
[0054] The difference between this embodiment and embodiment 3 is that "adding 0.04 g KH570" in step S3 is changed to "adding 0.06 g KH570"; the remaining raw materials and preparation process remain the same as those in embodiment 3.
[0055] Example 6
[0056] Compared with Example 4, the difference between this embodiment is that "the amount of APP@CS / Ag-g-PDEAMP is 0.25wt% of the total mass of the polylactic acid slice" is changed to "the amount of APP@CS / Ag-g-PDEAMP is 0.5wt% of the total mass of the polylactic acid slice"; the remaining raw materials and preparation steps remain the same as in Example 4.
[0057] Example 7
[0058] Compared with Example 4, the difference between this embodiment is that "the amount of APP@CS / Ag-g-PDEAMP is 0.25wt% of the total mass of the polylactic acid slice" is changed to "the amount of APP@CS / Ag-g-PDEAMP is 1wt% of the total mass of the polylactic acid slice"; the remaining raw materials and preparation steps remain the same as in Example 4.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that "DEAMP" in step S4 is changed to "MMP", that is, polymethyl methacrylate is grafted on the flame retardant and antibacterial agent; the other raw materials and preparation process remain the same as those in Example 1.
[0061] Comparative Example 2
[0062] In this comparative example, APP@CS / Ag was selected as a flame retardant and antibacterial agent;
[0063] The specific APP@CS / Ag was prepared by the following steps:
[0064] S1. APP and chitosan CS self-assemble to obtain APP@CS:
[0065] 1 g CS was dissolved in 1 wt% acetic acid solution to obtain CS solution, 10 g APP was evenly dispersed in 200 mL deionized water to obtain APP solution, the APP solution was added dropwise to the CS solution, stirred evenly, centrifuged, and washed with deionized water to obtain APP@CS;
[0066] S2. APP@CS complexes with Ag to form APP@CS / Ag:
[0067] 0.1 g APP@CS was added to 100 mL deionized water; then 16 mL of 10 mmol / L AgNO3 solution was added and stirred to mix; then 0.8 mL of 100 mmol / L NaBH4 solution was added dropwise and stirred to react for 15 min; ammonia water was added to adjust the pH value to alkaline so that a precipitate appeared in the solution, and the solution was centrifuged to obtain a solid substance. The solid substance was washed with distilled water, washed with acetone, and dried at room temperature for 12 h to obtain APP@CS / Ag.
[0068] The performance tests were performed on the polylactic acid fabrics obtained in Examples 1 to 7 and Comparative Examples 1 to 2. The vertical burning test (UL-94) was performed on the polylactic acid fabric according to the national standard GB / T2408-2021 to evaluate the flame retardancy of the polylactic acid fabric. The FZ / T73023-2006 standard was used to detect the antibacterial rate of the polylactic acid fabric against Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) to evaluate the antibacterial property of the polylactic acid fabric. The results are shown in Table 1:
[0069] Table 1
[0070]
[0071] It can be seen from Table 1 that the flame retardancy grades of the polylactic acid fabrics prepared in Examples 1 to 7 all reach V-0, indicating that the prepared polylactic acid fabrics all have excellent flame retardancy.
[0072] Compared with Example 1, Example 2 and Example 3, Example 3 has better antibacterial property, so it can be concluded that the increase of silver ion antibacterial agent is beneficial to improving the antibacterial property of the flame retardant antibacterial agent.
[0073] Compared with Example 3, Example 4 and Example 5, Example 4 has better antibacterial property, indicating that the dosage of KH570 should not be too low or too high. An appropriate amount of KH570 can provide sufficient reaction sites to promote the chemical bonding between chitosan and the silane coupling agent, thereby improving the activity and organophilicity of the chitosan surface, which is beneficial to the subsequent grafting reaction of DEAMP and improves the grafting efficiency and grafting density; however, when the amount of silane coupling agent is too much, it may cause excessive coverage of the chitosan surface to form a dense silane layer, which in turn hinders the DEAMP molecules from approaching the chitosan surface and reduces the grafting efficiency; thereby affecting the compatibility of the flame retardant antibacterial agent and polylactic acid.
[0074] Compared with Example 4, Example 6 and Example 7, Example 7 has better antibacterial property, indicating that increasing the amount of flame retardant and antibacterial agent is beneficial to improving the antibacterial property of polylactic acid fabric, and with the increase of the amount of flame retardant and antibacterial agent, the flame retardancy of polylactic acid fabric is not affected, indicating that the flame retardant and antibacterial agent has good dispersion in polylactic acid fabric, which is due to the grafting of DEAMP on the flame retardant and antibacterial agent, which improves the compatibility of the flame retardant and antibacterial agent with polylactic acid, thereby improving the dispersion of the flame retardant and antibacterial agent in polylactic acid.
[0075] Compared with Example 1, the flame retardancy of Comparative Example 1 is reduced, indicating that grafting phosphorus-containing acrylate on the flame retardant antibacterial agent can not only improve the compatibility of the flame retardant antibacterial agent and polylactic acid, but also play a flame retardant role. Compared with Example 1, the flame retardancy and antibacterial properties of Comparative Example 2 are reduced, indicating that APP@CS / Ag without grafting DEAMP cannot play a good flame retardant and antibacterial effect in polylactic acid, because APP@CS / Ag has low compatibility in polylactic acid, cannot be well dispersed, and is easy to agglomerate.
[0076] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production process for polylactic acid fabric, characterized in that: The steps include: The flame retardant antibacterial agent APP@CS / Ag-g-PDEAMP is melt-blended with polylactic acid slices to obtain flame retardant antibacterial polylactic acid slices; the flame retardant antibacterial polylactic acid slices are dried, melt-spun and woven to obtain polylactic acid fabrics.
2. The production process of a polylactic acid fabric according to claim 1, characterized in that: The preparation steps of the flame retardant antibacterial agent APP@CS / Ag-g-PDEAMP include: S1, ammonium polyphosphate and chitosan self-assemble to obtain APP@CS; S2, APP@CS complexed with Ag to form APP@CS / Ag; S3, silane coupling agent KH570 modified APP@CS / Ag to obtain APP@CS / Ag-KH570; S4. APP@CS / Ag-KH570 was grafted with poly(diethyl methylphosphonate) acrylate to obtain APP@CS / Ag-g-PDEAMP.
3. The production process of a polylactic acid fabric according to claim 2, characterized in that: The mass ratio of chitosan to ammonium polyphosphate in step S1 is 1:
10.
4. The production process of a polylactic acid fabric according to claim 2, characterized in that: The dosage ratio of APP@CS, AgNO3 solution and NaBH4 solution in step S2 is 0.1 g:16-20 mL:0.8-1 mL; the concentration of AgNO3 solution is 10 mmol / L, and the concentration of NaBH4 solution is 100 mmol / L.
5. The production process of a polylactic acid fabric according to claim 2, characterized in that: The amount of KH570 used in step S3 accounts for 4-6 wt % of APP@CS / Ag.
6. The production process of a polylactic acid fabric according to claim 2, characterized in that: In step S4, the APP@CS / Ag-KH570 and diethyl methylphosphonate acrylate monomer are mixed in a mass ratio of 1:1, and polydiethyl methylphosphonate acrylate is grafted under the action of an initiator azobisisobutyronitrile; the mass ratio of APP@CS / Ag-KH570 to azobisisobutyronitrile is 1:
40.
7. The production process of a polylactic acid fabric according to claim 6, characterized in that: In the synthesis process of the diethyl methylphosphonate acrylate monomer, the usage ratio of diisopropyl (hydroxymethyl)phosphonate, dichloromethane and triethylamine is 0.1 mol:50 mL:0.1 mol; and the usage ratio of acryloyl chloride to dichloromethane is 0.1 mol:10 mL.
8. The production process of a polylactic acid fabric according to claim 1, characterized in that: The temperature of the melt blending is 160°C-190°C; The amount of APP@CS / Ag-g-PDEAMP used is 0.25-1wt% of the total mass of the polylactic acid slice.
9. The production process of a polylactic acid fabric according to claim 1, characterized in that: The drying condition of the flame retardant and antibacterial polylactic acid slice is 110-120° C. for 10-12 hours; The melt spinning temperature is 180-200°C.
10. A polylactic acid fabric, characterized in that: Prepared by the production process described in any one of claims 1 to 9.
